Bioactive significance of fucoxanthin and its effective extraction. (July 2020) - Miyashita, Kazuo; Beppu, Fumiaki; Hosokawa, Masashi; Liu, Xiaoyong; Wang, Shuzhou
Abstract: Fucoxanthin (Fx) is a major carotenoid present in the chloroplasts of brown seaweeds and some kinds of microalgae. Because of the beneficial health effects of Fx, much attention has been focused on the considerable potential and promising applications of this compound in human health. Among the wide variety of biological activities of Fx, the interest has been mainly focused on its antiobesity effect, which is primarily based on the upregulation of thermogenesis through uncoupling protein 1 expression. Therefore, much effort has been made on the exploration for better Fx sources from different kinds of brown seaweeds and microalgae. The effective method to separate Fx has also attracted the interest of numerous researchers. Fx is conventionally extracted using organic solvents; however, solvents of petroleum origin are now strictly regulated worldwide. Thus, there is a growing demand for using greener, bio-based and renewable solvents for the extraction. From this viewpoint, edible oils may be promising green solvents. Edible oils can reduce the energy consumption in the extraction process and produce a barrier against Fx degradation. The edible oil extracts from brown seaweeds can be directly used as functional food materials containing Fx, without the need for purification.